Clinical paediatric dietetics - Shaw, Vanessa (Wiley-Blackwell, 2020)
"Clinical Paediatric Dietetics, Fifth Edition continues to provide a very practical approach to dietary management of children with an extensive range of disorders. Thoroughly revised to reflect the most recent scientific and medical literature, this new edition proves to be an indispensable guide for both acute and community-based healthcare professionals. New and expanded content covering a range of disorders, treatments and guidelines has been introduced to the fifth edition, from diabetes technology and the ketogenic diet, to renal tubular disorders, refeeding syndrome, and blended diets in enteral nutrition. This authoritative volume: Supports contemporary evidence-based clinical practice. Covers inherited metabolic disorders and diseases of all major organ systems. Provides contributions from practising paediatric dietitians, academic research dietitians and a paediatric psychiatrist Includes worked examples, real-world case studies and easy-to-use tables Endorsed by the British Dietetic Association, Clinical Paediatric Dietetics, Fifth Edition is an invaluable resource for all healthcare practitioners caring for children"- Resumé vydavatel
Keywords: výživa dětí; dietetika; děti; children's nutrition; dietetics; children; elektronické knihy; kolektivní monografie; electronic books; collective monographs